Method of Lines for Quasilinear Functional Differential Equations - Czernous, W.; Kamont, Z. (Український математичний журнал, 2013)
We give a theorem on the estimation of error for approximate solutions to ordinary functional differential equations. The error is estimated by a solution of an initial problem for a nonlinear functional differential equation. We apply this general result to the investigation of convergence of the numerical method of lines for evolution functional differential equations. The initial boundary-value problems for quasilinear equations are transformed (by means of discretization in spatial variables) into systems of ordinary functional differential equations. Nonlinear estimates of the Perron-type with respect to functional variables for given operators are assumed. Numerical examples are given. Наведено теорему про оцінку похибки наближених розв'язків звичайних диференціальних рівнянь. Похибка оцінюється за допомогою розв'язку початкової задачі для нелінійного функціонально-диференціального рівняння. Цей загальний результат застосовується при дослідженні збіжності числового методу ліній для еволюції функціонально-диференціальних рівнянь. За допомогою дискретизації по просторових змінних початково-крайові задачі для квазілінійних рівнянь зводяться до систем звичайних диференціальних рівнянь. Припускається справедливість нелінійних оцінок перронівського типу відносно функціональних змінних для заданих операторів. Наведено також чисельні приклади.